Effect of adalimumab on clinical outcomes and health-related quality of life among patients with ulcerative colitis in a clinical practice setting: Results from inspirADA - Travis, S; Feagan, BG; Peyrin-Biroulet, L; Panaccione, R; Danese, S; Lazar, A; Robinson, AM; Petersson, J; Pappalardo, BL; Bereswill, M; Chen, N; Wang, S; et al. (Oxford University Press, 2017)
Background and Aims Randomised trials have described the benefits of adalimumab [ADA] for ulcerative colitis [UC]; however, few data are available on health-related quality of life [HRQL] and health care costs in clinical practice. Methods InspirADA, a multicentre, prospective study, evaluated the effect of ADA in patients with moderate to severe UC treated according to usual clinical practice. Outcomes assessed were: Simple Clinical Colitis Activity Index [SCCAI] response/remission rates; changes in HRQL; all-cause direct costs; and UC-related direct and indirect costs from baseline to Week 26. Results Data from 463 patients were analysed. At Week 26, 67% (95% confidence interval [CI]: 62%, 71%) of patients achieved response; 48% [95% CI: 44%, 53%] were in remission. For the overall population, significant [all p < 0.001] improvements from baseline to Week 26 were observed for the Short Inflammatory Bowel Disease Questionnaire [SIBDQ] (mean change ± standard deviation [SD]: 17.4 ± 14.5) and the European Quality of Life—5 Dimensions—5 Level [EQ-5D-5L] (index: 0.1 ± 0.2; visual analogue scale [VAS]: 19.5 ± 25.8). Parallel improvements were seen in work productivity [11% absolute decrease in absenteeism; 25% absolute decrease in impairment while working; and 27% absolute decrease in impairment of ability to perform daily activities, all p < 0.001]. Among study completers, cumulative all-cause medical costs and UC-related medical costs were significantly [both p < 0.001] reduced by 59% and 77%, respectively, 6 months after initiation of therapy compared with the preceding 6 months. The safety profile of ADA was consistent with that observed in previous clinical trials. Conclusions ADA therapy in usual clinical practice is effective at improving and maintaining symptomatic control, improving HRQL, and decreasing costs of medical care among patients with UC.